Design Rules for Polymer Blends with High Thermoelectric Performance. Issue 19 (7th April 2022) - Zapata‐Arteaga, Osnat; Marina, Sara; Zuo, Guangzheng; Xu, Kai; Dörling, Bernhard; Pérez, Luis Alberto; Reparaz, Juan Sebastián; Martín, Jaime; Kemerink, Martijn; Campoy‐Quiles, Mariano
Abstract: A combinatorial study of the effect of in‐mixing of various guests on the thermoelectric properties of the host workhorse polymer poly[2, 5‐bis(3‐tetradecylthiophen‐2‐yl)thieno[3, 2‐b]thiophene] (PBTTT) is presented. Specifically, the composition and thickness for doped films of PBTTT blended with different polymers are varied. Some blends at guest weight fractions around 10–15% exhibit up to a fivefold increase in power factor compared to the reference material, leading to zT values around 0.1. Spectroscopic analysis of the charge‐transfer species, structural characterization using grazing‐incidence wide‐angle X‐ray scattering, differential scanning calorimetry, Raman, and atomic force microscopy, and Monte Carlo simulations are employed to determine that the key to improved performance is for the guest to promote long‐range electrical connectivity and low disorder, together with similar highest occupied molecular orbital levels for both materials in order to ensure electronic connectivity are combined. Abstract : A high throughput study of the thermoelectric properties of polymer mixtures is presented. Varying the composition and employing thickness gradients, nearly 200 samples are characterized locally. Mixtures of poly[2, 5‐bis(3‐tetradecylthiophen‐2‐yl)thieno[3, 2‐b]thiophene] with 10–15 wt% of a guest material show a fivefold increase in power factor, which is ascribed to an improvement in morphology and a similar energy landscape between the two polymers.